RANCANG BANGUN MEJA DAN RAK PENYIMPANAN JOINT SLEEVE DILENGKAPI ALAT UKUR BERBASIS SENSOR ULTRASONIK - Purwita Sary, Indri; Ahmad, Fauzi; Sunarko, Agus (Jurnal Sains Ilmu Teknologi Industri, 2023)
Non-Value Added activities and non-ergonomic working conditions can result in reduced productivity. in this case the Dept. Raw Edge PT XYZ has problems in the curing process where at the time of installation of the joint sleeve there are non-value added activities such as searching and checking. The conditions of storage racks and work tables that are not ergonomic make it difficult for operators to store the joint sleeve according to their identity so that when they want to take the joint sleeve, a search and inspection process occurs with a time of 231 seconds. This study aims to create a design to assist operators in retrieving, storing and reaching the joint sleeve by making more ergonomic tables and shelves, improving shelf identity and making ultrasonic sensor-based measuring instruments. There are 3 non-value added activities, namely reaching, searching and checking. Obtained an ergonomic table size with a length of 80cm, width 110cm and height 90cm as well as the division of shelf size classifications, namely <8cm, 8-12cm, and >29cm